2018
DOI: 10.1111/liv.13973
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors in non‐alcoholic fatty liver disease

Abstract: Background & Aims Patients with non‐alcoholic fatty liver disease (NAFLD) are at an increased risk for cardiovascular disease (CVD). It is unclear whether histological variables may help predict CVD risk. We evaluated histology and traditional CV risk factors as predictors of CVD outcomes in a large NAFLD cohort. Methods We included 603 biopsy‐proven NAFLD patients free of baseline CVD and matched these (1:10, by age, sex and municipality) to 6269 population controls. All individuals were cross‐linked to natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 27 publications
(58 reference statements)
3
67
0
1
Order By: Relevance
“…One possible explanation for this finding is that patients with ASCVD ≥7.5% already have an increased risk for cardiac-specific mortality and so the presence of advanced fibrosis does not seem to add additional risks. Our finding is supported by a recent study by Hagstrom et al (40) , which evaluated liver histology and traditional cardiovascular risk factors as a predictor of CVD outcomes in patients with biopsy-proven NAFLD. This study concluded that when CVD risk factors were taken into account, the presence of nonalcoholic steatohepatitis or advanced fibrosis was not associated with incident CVD risk in patients with NAFLD.…”
Section: Discussionsupporting
confidence: 88%
“…One possible explanation for this finding is that patients with ASCVD ≥7.5% already have an increased risk for cardiac-specific mortality and so the presence of advanced fibrosis does not seem to add additional risks. Our finding is supported by a recent study by Hagstrom et al (40) , which evaluated liver histology and traditional cardiovascular risk factors as a predictor of CVD outcomes in patients with biopsy-proven NAFLD. This study concluded that when CVD risk factors were taken into account, the presence of nonalcoholic steatohepatitis or advanced fibrosis was not associated with incident CVD risk in patients with NAFLD.…”
Section: Discussionsupporting
confidence: 88%
“…115 A recent Swedish cohort study in liver biopsy-diagnosed NAFLD with the longest documented follow-up time (of over 18 years) supported these findings by showing that patients with NAFLD are at an increased risk for CVD. 116 Although more studies are needed to confirm a causal relationship between NAFLD and CVD, these findings highlight Meta-analysis showing an association of NAFLD with major adverse CVD events 34 studies with a total of 164,494 participants were included; specifically, 21 crosssectional studies and 13 cohort studies were examined in this meta-analysis NAFLD was not associated with overall mortality and CVD mortality but was, however, associated with an increased risk of prevalence and incidence of CVD Hagström et al…”
Section: Cardiovascular Outcomes and Mortality In Nafldmentioning
confidence: 99%
“…Other studies, like the one in the aforementioned meta‐analysis, have identified fibrosis as the best predictor of long‐term survival, with increased cardiovascular mortality in patients with advanced fibrosis . Yet, data on the relationship between fibrosis and CVD have also been inconsistent, and many of these prior studies were limited by either a retrospective design, a small number with advanced fibrosis, or inclusion of individuals with pre‐existing CVD . Furthermore, nearly all of these studies assessed cardiovascular mortality; few evaluated the development of incident fatal and nonfatal CVD as an outcome.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,5 Yet, data on the relationship between fibrosis and CVD have also been inconsistent, and many of these prior studies were limited by either a retrospective design, a small number with advanced fibrosis, or inclusion of individuals with pre-existing CVD. 13,14 Furthermore, nearly all of these studies assessed cardiovascular mortality; few evaluated the development of incident fatal and nonfatal CVD as an outcome.…”
Section: Introductionmentioning
confidence: 99%